Devoção e resistência: as Irmandades de Homens Pretos de Goiana (1830-1850) - Silva, Maria de Jesus Santana (2009)
The Black Brotherhoods of Goiana were advocates of devotion and defenders of religious and african cultural traditions. This study considers them under three perspectives: as diverse forms of collective representations and expressions of the sacred; as a technique in societal control by catholic authorities; and, as syncretism while simultaneously being a mythical-symbolical strategy of resistance. In this historical reconstruction, the Black Brotherhoods reveal their sacred and black cultural reminiscences in their feasts, processions and funerals. The strong control exercised by both Church and State over the Brotherhoods forced the black man to create collective representations, ways to organize so that he could preserve his ethos. This happened at the same time when it was possible for him to affirm his identity in a social and cultural space as resistance. In this perspective, syncretism, as lived in the Black Brotherhoods, was a significant force in maintaining african traditions